New profiles of agricultural enterprises as an expansion of agricultural law - Victoria, María Adriana (Przegląd Prawa Rolnego, 2022)
This work aims to address the new profiles of agricultural enterprises (subject, object, activity) and legal requirements of environmental law and food law, with particular focus on the expansion of agricultural law.